Competitiveness of sharing economy companies in emerging markets. Issue 2 (10th April 2020) - Maalouf, Jamal T.; Abi Aad, Amine; El Masri, Karam
Abstract : Purpose: This paper aims to explore the competitiveness of the sharing economy in emerging markets from the perspective of actual and potential consumers. Design/methodology/approach: It is not surprising that most sharing economy businesses may not follow traditional competitiveness approaches. Consequently, their entry strategies and competitiveness methods might face modern, unique and unexpected challenges vis-à-vis securing sufficient consumer willingness to purchase goods and services. Findings: A novel theoretical research model is developed which posits that people's willingness to use the sharing economy is negatively related to liabilities of newness and positively related to consumer innovativeness and interpersonal trust. The relationship between cost and willingness to use is likely to vary on a case-by-case basis depending on the nature and extent of substitutes available or, in other words, the novelty or lack thereof embedded in the particular good or service. Other potential determinants are also best viewed as case-specific such as ethical/sustainability concerns, which vary as a function of target consumers' preferences for ameliorating social and environmental externalities. Originality/value: Sharing economy businesses have expanded to numerous countries around the world. There is growing evidence to suggest that this diffusion will most likely be maintained. The competitiveness of these businesses in emerging markets may depend on several variables but there is a dearth of literature in this domain which this paper seeks to address while concomitantly highlighting important avenues for future research.